The MICA deletion across different populations - de Oliveira Ciriaco, Viviane Aparecida [UNESP]; Rodrigues, Amanda Muniz [UNESP]; da Silva Tibúrcio, Brenda Caroline [UNESP]; Silva, Joyce Machado [UNESP]; Naslavsky, Michel Satya; Mendes-Junior, Celso Teixeira; Bannwart Castro, Camila Ferreira [UNESP]; Castelli, Erick C. [UNESP] (Elsevier, 2024)
The MICA gene encodes a glycoprotein upregulated upon cellular stress, particularly in oxidative stress, intracellular infections, and tumorigenesis. This stress-signaling molecule interacts with the activating receptor NKG2D from Natural Killer (NK) and some T lymphocytes, stimulating their cytotoxic activity. MICA is encoded within the human Major Histocompatibility Complex next to the HLA-B locus and is highly polymorphic. MICA might be absent from chromosome 6 due to a large deletion of approximately 100 Kb between HLA-B and MICB. Therefore, some individuals may not produce any isoform of MICA. The distribution of this phenotype may vary among different populations. We evaluated the distribution of the MICA*del and other MICA null alleles in different biogeographic regions and the Linkage Disequilibrium (LD) pattern between this allele and HLA-B. We detected at least two different patterns of deletion, one with full deletion of MICA and surrounding sequences and one partial MICA deletion. The presence of different patterns of deletion suggests independent deletion events. We confirm that the previously described MICA*del allele is mainly associated with B*48 and MICB*009N in Asia and America, but other haplotypes also occur. While most samples with complete or partial MICA deletion are heterozygous and present one functional copy of both MICA and MICB genes, we detected two samples with no functional MICA and one with no functional MIC genes. Therefore, other mechanisms might be in place to compensate for the absence of MIC molecules.
Keywords: Deletion; Duplication; MICA; MICB